From cash to cashless: The Impact of Cashless Payment Adoption on Student Spending Behavior in Malaysia - Hang, Annie Wong Pooi; Singh, Padmalini; Huei, Lok Yee; Kesvaran, Yoshanaa A/P Elang; Dajun, Yu; Shengpu, Yu; Zixin, Yu; Kee, Daisy Mui Hung (The Global Academia Publisher, 2025)
Modern innovation is expanding rapidly in Malaysia in line with current developments and practices. Consequently, cashless payment methods are increasingly preferred by the community for daily transactions. Previous observations indicate that students tend to purchase more non-essential items when using cashless payment methods. This behavior occurs because payments made through cards or mobile devices are perceived as more effortless compared to traditional cash transactions. Therefore, this study examines the impact of cashless payment adoption on the spending behavior of university students in Malaysia. Specifically, the study aims to analyze how convenience, consumer habits, social influence, and perceived security influence students’ budgeting practices, financial discipline, and impulsive spending behavior. Data were collected from 153 undergraduate students enrolled in public and private universities through an online survey administered via Google Forms. Data analysis was conducted using SPSS, including descriptive analysis, correlation analysis, and regression analysis. The findings provide important insights for educators and fintech companies in developing financial education programs tailored to the cashless economy.